Prophylactic bilateral Salpingo-oophorectomy and eventual development of endometrial cancer: Two individual case reports - Sophia Halassy; Katrina Au; Vinay Malviya; Janet Mullings-Britton (Elsevier, 2020)
Prophylactic bilateral salpingo-oophorectomy (PBSO) is regularly performed when patients have a high risk of developing ovarian cancer (i.e. a personal or family history). Most commonly, PBSO is performed in pre-menopausal women who have completed childbearing. The major risk of uterine preservation is future development of endometrial cancer. We report two cases that highlight such occurrences in women who believed that the uterus was important for sexual function. The misunderstanding that the uterus is important for sexual satisfaction should be thoroughly discussed and rectified prior to initial surgery. This is especially important in patients who may eventually require hormone replacement therapy. Keywords: Risk-reducing bilateral salpingo-oophorectomy, Endometrial cancer, Genetic predisposition, Genetic counseling